REVITALIZING UZBEKISTAN'S HERITAGE: THE POTENTIAL OF ECOTOURISM IN SPECIALLY PROTECTED NATURAL AREAS (Scientific Journal of Actuarial Finance and Accounting, 2024)
Uzbekistan's protected areas, rich in biodiversity and cultural heritage, are increasingly attracting global tourists. However, this surge in tourism poses threats to the environment and local cultures. Ecotourism, which emphasizes sustainable practices and community involvement, offers a solution. This paper examines the principles of ecotourism and their application in Uzbekistan, providing a detailed review of the literature and defining key concepts. It explores how ecotourism can be integrated into Uzbekistan's tourism sector through technological advancements and stakeholder collaboration. By highlighting successful examples and identifying areas for improvement, the paper outlines strategies for developing a balanced and sustainable ecotourism industry that benefits both the environment and local communities.